Quantifying the prevalence of energy poverty across Canada: Estimating domestic energy burden using an expenditures approach - Das, Runa R.; Martiskainen, Mari; Li, Grace (The Canadian geographer, 2022)
Energy poverty is gaining public attention in Canada. Based on statistical analysis of Statistics Canada's 2016 Survey of Household Spending, we estimate that 7–9% of households spent more than 10% of their income on energy expenditures. Households in the Atlantic provinces faced the most energy poverty and highest energy expenditures. Low income, geography, and dwelling conditions were the main predictors of energy poverty. Households in energy poverty also spent approximately five times more on energy expenditures as a proportion of their total expenditures compared to households not in energy poverty. Our study fills a key research gap as a limited number of studies exist on the extent and drivers of energy poverty in Canada. Further, our study's robust quantitative estimates allow benchmarking and comparative research. These estimates lay the groundwork for evidence‐based solutions—and our findings highlight the need to reconsider current policies. Considering the challenge of the ratio of energy costs to income is vital, especially in the aftermath of events such as COVID‐19 or the 2021 heatwave in western Canada, which result in different energy behaviours and needs. More broadly, in the regular day‐to‐day, energy services should be seen as necessary and decision makers ought to consider the energy burden of Canadians. Key messages Research on energy poverty in Canada is an understudied area in Canadian scholarship. Energy poverty is studied by examining the ratio of household energy expenditures to household income. Households in energy poverty spent more on energy expenditures as a proportion of their total expenditures compared to households not in energy poverty. La prévalence de la pauvreté énergétique au Canada : L'estimation du poids financier de l'énergie domestique selon l'approche axée sur les dépenses Le phénomène de pauvreté énergétique attire de plus en plus l'attention au Canada. À partir des données de l'Enquête sur les dépenses des ménages de Statistique Canada (2016), nous estimons qu'entre 7 et 9% des ménages ont engagé plus de 10% de leurs revenus en dépenses énergétiques. Selon nos analyses, les ménages des provinces de l'Atlantique connaissent la plus importante pauvreté énergétique et les dépenses énergétiques les plus élevées. De plus, le faible revenu, la localisation et les conditions de logement sont les principales variables explicatives de la pauvreté énergétique. Finalement, les ménages en situation de pauvreté énergétique ont engagé environ cinq fois plus d'argent en dépenses énergétiques proportionnellement à leurs dépenses totales, si on les compare aux autres ménages. En conséquence, notre étude comble une lacune de la recherche puisqu'il n'existe qu'un nombre limité d'études sur la portée et les facteurs de la pauvreté énergétique au Canada. Par ailleurs, les traitements quantitatifs approfondis de notre enquête permettent de faire un étalonnage et une démarche comparative. Ces résultats jettent les bases de solutions fondées sur des données probantes car nos conclusions mettent également en évidence la nécessité de réexaminer les politiques actuelles. Au final, il est essentiel de reconnaître l'importance du problème du ratio des coûts énergétiques, particulièrement à la suite d'événements tels que la COVID‐19 ou les canicules, lesquels ont eu pour effet de modifier les comportements et les besoins énergétiques.